Innovation management and growth in emerging economies - Webb, Heather C., 1979-; Wu, Wendy, 1973-; Al Numairy, Hussain A., 1986- (Advances in business strategy and competitive advantage., 2021)
"This book showcases how innovations from emerging economies are being developed through strategic choices and the knowledge being created is aiding practitioners and researchers as it provides fresh insights to broaden their horizons with different contextual issues , allowing them to interact to shape and define either new institutions or new industries"--